(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and laboratory characteristics and the treatment outcomes of patients with cytomegalovirus associated thrombocytopenia at the Clinical Hematology Department - National Children’s Hospital. Subjects: Seventy-six patients under 18 years old diagnosed with CMV-associated thrombocytopenia and treated at the Clinical Hematology Department - National Children’s Hospital, of whom treatment outcomes were evaluated in 74 patients who were followed up during treatment. Methods: Descriptive case series. Results: CMV associated thrombocytopenia in this study was mostly observed in children under 12 months of age, accounting for 80.3%. Males were more common than females. The most common symptom was bleeding (100%), anemia (53.9%). Other symptoms were also recorded such as diarrhea (30.3%) and respiratory tract infection (22.3%). Most patients had severe thrombocytopenia <20 G/L (88.2%). The CMV viral load in blood was inversely proportional to the platelet count. Clinical course types included: acute (82.4%), persistent (10.8%), and chronic (6.8%). Complete, partial, and no response rates to treatment were 55.4%, 43.2%, and 1.4%, respectively. Ten patients with CMV-associated thrombocytopenia had complicated clinical manifestations (hepatitis, bronchitis, fever, etc.) and did not respond to initial treatment with corticosteroids, intravenous immunoglobulin; after ganciclovir was added to the regimen, 9 out of 10 patients responded to treatment. Conclusion: Patients with CMV-associated thrombocytopenia were mainly infants under 12 months of age, with the most common clinical manifestation being bleeding, followed by anemia. Most patients had severe thrombocytopenia (<20 G/L) and the platelet count decreased as the viral load increased. Antiviral therapy should be added for patients who do not respond to standard immune thrombocytopenia therapy.